# pre calculus

Change the exponentioanl expression to an equivalent expression involving a logarithm. e^-1/3 = 9t

1. take the natural log (ln ) of each side.

-1/3=ln(9t)

posted by bobpursley
2. I can't believe it's that simple, I have been going crazy! Thank you!

posted by anon

## Similar Questions

change the exponential expression to an equivalent expression involving a logarithm. 1.9=a^6 a=1.1129 is this the correct logarithmic expression???
2. ### pre-cal

change the exponential expression to an equivalent expression involving a logarithm. 4.1=a^2
3. ### precalulus

Change the exponentional expression to an equivalent expression involving a logarithm. 7^c = 0.026
4. ### Algebra HELP

Change the exponentional expression to an equivalent expression involving a logarithm. (2x)^-10=4
5. ### math

change the exponential expression to an equivalent expression involving a logarithm. 8.8=7^x please show work
6. ### calculus

Change the exponential expression to an equivalent expression. It should involve an a logarithm. 6.5=a^3 This is what I have. can you help me out. Ina[1/3]In6.5
7. ### Math - changing logarithmic expression

Change the logarithmic expression to an equivalent expression involving an exponent. Log1/5(1/625) = C
8. ### prcalculus

change the logarithmic expression to an equivalent expression involving an exponent. log416=x
9. ### alg

change the logarithmic expression to an equivalent expression involving an exponent. 4^16=x log (base4)16=x is it x=e^2?
10. ### algebra

change the logarithmic expression to an equivalent expression involving an exponent. 4^16=x log (base4)16=x is it x=e^2?

More Similar Questions